The Psychometric Properties of the Norwegian version of Brief Problem Monitor (BPM) - Backer-Grøndahl, Agathe; Martinussen, Monica (PsykTestBarn, 2018)
Descriptive: Brief Problem Monitor (BPM) is a screening instrument for monitoring children’s functioning in different problem areas (externalizing problems, internalizing problems, and attention problems), as well as for assessing responses to therapeutic interventions. It is a short version of the Achenbach System of Empirical Based Assessment (ASEBA) forms for children and youths aged 6–18 years. Separate BPM forms were developed for different informants: parents (BPM-P), teachers (BPM-T), and a self-report form for youths (BPM-Y). The BPM items (19 items; 18 in the BPM-T) were selected from the corresponding longer ASEBA scales (i.e., CBCL, TRF, and YSR). The BPM was developed by Achenbach et al. (2011). The Norwegian BPM-items were derived from the translations of the CBCL, TRF, and YSR by Torunn S. Nøvik and Sonja Heyerdahl, published in 1986/88, 1993, and 2002, respectively (Kornør & Jozefiak, 2012). Literature search: The systematic literature search yielded only one study that reported results on the BPM in a Norwegian sample. The study reports analyses of internal consistency (reliability) and validity of the BPM in two large population-based samples of school-age children (4th -10th grades and 1st-7th grades). Psychometrics: The results suggest good reliability for the total problem scale across reporters, while the reliability coefficients are substantially lower for some of the subscales; in particular, for the BPM-Y. Correlation coefficients between the subscales and corresponding scales in the longer versions indicate good construct validity. Conclusion: The BPM may provide useful information regarding behavioral and emotional problems in children and youths. However, more studies on Norwegian or Scandinavian samples are needed to examine the adequacy of the psychometric properties of the Norwegian versions of BPM. Also, as the BPM was developed to monitor children’s functioning over a period of time, including their responses to interventions, more studies are needed that focus on - or include - these aspects.